IDENTIFYING FACTORS WHICH PREDICT WOMEN’S INABILITY TO MAINTAIN SEPARATION FROM AN ABUSIVE PARTNER - Alhalal, Eman (2011)
In the aftermath of intimate of partner violence (IPV), women often experience a number of intrusive issues including abuse and harassment, the demands of managing health problems, the personal cost of getting help, and changes to patterns of living. Although these challenges in women’s lives could explain why they return to their ex-partners or engage in a new abusive relationship, the full range o f conditions which interfere with women’s ability to maintain separation from an abusive partner have not been identified. This study examines the extent to which selected indicators of intrusion predict the odds of women maintaining separation from an abusive partner over a 1 year period of time by testing a hypothesis derived from Strengthening Capacity to Limit Intrusion theory. This secondary analysis of 286 women who completed both wave 1 and 2 from the Women’s Health Effects Study revealed that depression and PTSD heighten women’s risk of their inability to maintain separation from an abusive partner. The finding of this study emphasizes the importance of adapting nursing’s practice, education, and research focus to ultimately care for abused women in terms of mental health